A Legal Analysis of The Bandung Administrative Court Decision No. 180/G/2024/Ptun.Bdg Regarding A Dispute Over The Transfer of Civil Servants from The Perspective of The General Principles of Good Governance - Faza Pauzia Hermawan; Ifqi Maula Manaz; Sanabila Khairil Ahya; Siti Maharani; Taufiq Alamsyah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the legality of Bandung Administrative Court Decision Number 180/G/2024/PTUN.BDG concerning a dispute over the transfer of a civil servant position through the perspective of the General Principles of Good Governance. The research employed a non empirical normative juridical approach based on statutory analysis, case analysis, and conceptual analysis. Primary sources consisted of the court decision and relevant Indonesian administrative law regulations governing state administrative justice, government administration, and the state civil apparatus. The findings indicate that the disputed transfer decision was issued by a competent authority but contained significant procedural and substantive defects. The court identified the use of an expired technical recommendation, administrative error, insufficient objective justification, and non compliance with merit based personnel management standards. These deficiencies resulted in violations of legal certainty and due care principles that form essential components of good governance. The analysis further demonstrates that the General Principles of Good Governance function as substantive standards for reviewing administrative discretion beyond formal legality. The decision strengthens judicial oversight, promotes bureaucratic accountability, reinforces merit system implementation, and contributes to the development of governance oriented administrative law in Indonesia.